Behavioral plasticity mitigates the effect of warming on white‐tailed deer. Issue 5 (11th February 2020) - Wolff, Carter L.; Demarais, Stephen; Brooks, Christopher P.; Barton, Brandon T.
Abstract: Climate change is expected to create novel environments in which extant species cannot persist, therefore leading to the loss of them and their associated ecological functions within the ecosystem. However, animals may employ behavioral mechanisms in response to warming that could allow them to maintain their functional roles in an ecosystem despite changed temperatures. Specifically, animals may shift their activity in space or time to make use of thermal heterogeneity on the landscape. However, few studies consider the role of behavioral plasticity and spatial or temporal heterogeneity in mitigating the effects of climate change. We conducted experiments to evaluate the potential importance of behavior in mediating the net effects of warming on white‐tailed deer ( Odocoileus virginianus ). We used shade structures to manipulate the thermal environment around feeding stations to monitor deer feeding activity and measure total consumption. In individual experiments where deer only had access to unshaded feeders, deer fed less during the day but compensated by increasing feeding during times when temperature was lower. In group experiments where deer had access to both shaded and unshaded feeders, deer often fed during the day but disproportionally preferred the cooler, shaded feeders. Our results suggest that deer can capitalize on temporal and spatial heterogeneity in the thermal environment to meet nutritional and thermal requirements, demonstrating the importance of behavioral plasticity when predicting the net effects of climate change. Abstract : Animal behavior may mediate the net effects of climate change within ecosystems but is largely ignored in climate change research. We conducted experiments with shaded feeders to evaluate how temperature alters feeding behavior of white‐tailed deer. Our results show that deer can alter their behavior to take advantage of spatial and temporal heterogeneity in temperature to maintain their functional role as herbivores.